2018
DOI: 10.5505/.2018.65487
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation Of Compassion Level Of Nursing Students In A Health College (Turkish)

Abstract: Object: The aim of this study is to determine the level of compassion and the factors that affect the level of compassion of nursing students in a health college. Methods: The descriptive study has been conducted in a nursing department of a health college. "Introductory Information Form" by the researchers in accordance with the literature and developed by Pommier (2010) "Compassion Scale" has been used as the data collection tool. Analyzes of the data were conducted by using frequency, Mann-Whitney U Test, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The statistical results showed that the level of compassion of females is higher than that of males. While the result of this study showed similarity with those reported in the study carried out by Sacco and Copel, 33 it differed from several other studies 10,37 . It is thought that women's maternal role, emotional structures, cultural teachings and social responsibilities increase their level of compassion.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The statistical results showed that the level of compassion of females is higher than that of males. While the result of this study showed similarity with those reported in the study carried out by Sacco and Copel, 33 it differed from several other studies 10,37 . It is thought that women's maternal role, emotional structures, cultural teachings and social responsibilities increase their level of compassion.…”
Section: Discussionsupporting
confidence: 55%
“…While the result of this study showed similarity with those reported in the study carried out by Sacco and Copel, 33 it differed from several other studies. 10,37 It is thought that women's maternal role, emotional structures, cultural It was determined that marital status did not affect levels of compassion. Kiwol et al 35 reported that the level of compassion was high in married nurses, but the difference was not significant.…”
Section: Compassionmentioning
confidence: 99%
See 1 more Smart Citation